A Decade of Poverty Reduction in Kazakhstan 2001–2009: Growth and/or Redistribution?. (4th April 2017) - Kudebayeva, Alma; Barrientos, Armando
Abstract: This paper examines the factors explaining the sustained fall in poverty experienced in Kazakhstan in the period 2001–2009. It examines the contribution of economic growth and redistribution policies to poverty reduction through an analysis of household survey data. It finds that growth has been strongly pro‐poor. Growth was the main driver behind the fall in poverty in the first half of the decade, but redistribution gained in importance in the latter part of the decade. Copyright © 2017 John Wiley & Sons, Ltd.